2009
DOI: 10.1039/b820829h
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated anthracene derivatives as donor materials for bulk heterojunction solar cells: olefinic versus acetylenic spacers

Abstract: Substituting olefinic for acetylenic pi-spacers in anthracene-based conjugated semiconductor donors leads to appreciable increases in the power conversion efficiencies of the resulting bulk heterojunction solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 26 publications
1
82
0
2
Order By: Relevance
“…In 2009, Marrocchi et al [84] reported a series of anthracene-based derivatives 26a-d. It was found that the replacement of the acetylenic for the olefinic as the π-bridge leads to a considerable increases in PV performance.…”
Section: π-Linkage With Alkynementioning
confidence: 99%
“…In 2009, Marrocchi et al [84] reported a series of anthracene-based derivatives 26a-d. It was found that the replacement of the acetylenic for the olefinic as the π-bridge leads to a considerable increases in PV performance.…”
Section: π-Linkage With Alkynementioning
confidence: 99%
“…More recently, anthracene derivatives have been used as donor materials for bulk heterojunction solar cells. [29] Kamat reported the sensitization of anthracene-9-carboxylic acid (9-AC) to sensitize a diluted (0.05 to 2 mm) acetonitrile colloidal suspension of TiO 2 nanoparticles 30 nm in diameter, using the injected electron to reduce oxazine 725 (N,N,N',N'-tetraethyloxonine) in a stepwise electron transfer process ( Figures 5 and 6). [30] The negative oxidation potential of the excited singlet state of 9-AC (9-AC*(S 1 ) % À1.8 V vs. NHE) compared to the conduction band of the semiconductor provided favorable energetics for the sensitization, and the COOH group was used to anchor the molecule to the surface of the semiconductor.…”
Section: The Anchoring Groups and Linkersmentioning
confidence: 99%
“…Among rigid fused aromatic entities, anthracene has been widely used in opto-electronic materials such as organic thin film transistors [22][23][24], organic light-emiting diodes [25][26][27][28][29][30] and bulk heterojunction solar cells [31]. Recently, a few anthracene-based derivatives have been reported as sensitizers for DSSCs [32][33][34].…”
Section: Open Accessmentioning
confidence: 99%